Elevated Seawater Temperatures Decrease Microbial Diversity in the Gut of Mytilus coruscus - Li, Yi-Feng; Yang, Na; Liang, Xiao; Yoshida, Asami; Osatomi, Kiyoshi; Power, Deborah; Batista, Frederico M.; Yang, Jin-Long (Frontiers in Physiology, 2018)
The gut microbial community is critical for the host immune system, and in recent years it has been extensively studied in vertebrates using ‘omic’ technologies. In contrast, knowledge about how the interactions between water temperature and diet affect the gut microbiota of marine invertebrates that do not thermoregulate is much less studied. In the present study the effect of elevated seawater temperature and diet (Isochrysis zhanjiangensis and Platymonas helgolandica var. tsingtaoensis) on the gut microbial community of the commercial mussel, Mytilus coruscus, was investigated. 16S rRNA gene sequencing was used to characterize the microbial community in M. coruscus gut. The mortality of M. coruscus exposed to a high water temperature (31˚C) increased after three days and the diversity of the bacterial community in the gut of live M. coruscus was significantly reduced. For example, the abundance of Bacteroides (Bacteroidetes) and norank_Marinilabiaceae (Bacteroidetes) increased in the gut of M. coruscus fed I. zhanjiangensis. In M. coruscus fed P. helgolandica the abundance of Arcobacter (Proteobacteria) and norank_Marinilabiaceae increased and the abundance of unclassified_Flavobacteriaceae (Bacteroidetes) decreased. The results obtained in the present study suggest that high temperatures favoured the proliferation of opportunistic bacteria, including Bacteroides and Arcobacter, which may increase host susceptibility to disease. Microbial community composition of the gut in live M. coruscus was not impacted by the microalgal diet but it was modified in the group of mussels that died. The present study provides insight into the potential effects on the gut microbiome and mussel - bacteria interactions of rising seawater temperatures.